Dark Patterns: Understanding Consumer Awareness & Regulatory Mechanism (Don Bosco Institute of Technology Delhi Journal of Research, 2025)
Persuasive interface designs are gaining a lot of importance in directing user  behavior on digital platforms. While many of th tactics which forms part of  the interface are important & also within the legal boundaries, other design  practices—known as “dark patterns”—cross ethical boundaries and are used  purposively for deceiving the consumers through various social media channels.  Three main aspects are examined in this conceptual paper: (1) the meaning and  types of dark patterns; (2) the extent to which consumers are aware of these  trends when using online platforms; and (3) the level of awareness among  users regarding the legal protections and regulatory framework available  against manipulative dark patterns used digitally . The paper focused on how  consumers are actually aware of the various types of dark patterns used on the  digital platforms.The research paper is beneficial for the consumers as it creates  awareness among them, for policymakers on how to create a user friendly digital  user interface for digital literacy.
Keywords: Dark Patterns Con sumer Awareness, Regulatory, Digital Platforms